Zinc oxide/silver bimetallic nanoencapsulated in PVP/PCL nanofibres for improved antibacterial activity. (18th August 2018) - Hu, Min; Li, Chenwen; Li, Xin; Zhou, Min; Sun, Jianbin; Sheng, Fangfang; Shi, Sanjun; Lu, Laichun
Abstract: The anti-infection ability and skin regeneration are important aspects on the progress of wound healing, which needs an ideal wound dressing that not only resists bacteria but also promotes skin regeneration. In this study, zinc oxide/silver/polyvinylpyrrolidone/polycaprolactone (ZnO/Ag/PVP/PCL) nanofibres were prepared through electrospinning. Firstly, zinc oxide nanoparticles (ZnONPs) and silver nanoparticle (AgNPs) were synthesized respectively. Secondly, the two nanoparticles were mixed with polyvinylpyrrolidone (PVP) and polycaprolactone (PCL) to obtain the nanofibres. The results of scanning electron microscopy (SEM) showed that ZnONPs and AgNPs were 40.07 ± 9.70 nm and 37.46 ± 12.02 nm, respectively. After electrospinning, the nanofibres were 368.22 ± 123.96 nm in diameter. Infrared spectroscopy revealed that ZnONPs/AgNPs bimetallic nanomaterials were physically embedded in the nanofibres. The antibacterial effects against Staphylococcus aureus and Escherichia coli of ZnO/Ag/PVP/PCL nanofibres were significantly better than these of the single metal material-loaded nanofibres. More importantly, the combination of ZnO and Ag reduced the cytotoxicity of ZnO/Ag/PVP/PCL bimetallic nanofibres toward fibroblasts. These findings demonstrated that ZnO/Ag/PVP/PCL bimetallic nanofibres should be of greater interest than the single metal nanomaterial-loaded nanofibres in inhibiting growth of bacteria.